ADOPTION STRATEGY OF IFRS SUSTAINABILITY DISCLOSURE STANDARDS TOWARD REALIZATION OF COMPREHENSIVE CORPORATE REPORTING - Muhammad Fitrah Mahaini (IPSAR (International Public Sector Accounting Review), 2023)
Accountants is one of the main actors to developing the standards and policy of company reporting. IFRS Foundation initiated the establishment of International Sustainability Standard Board (ISSB) which will develop IFRS Sustainability Disclosure Standards (IFRS-SDS). IFRSSDS is expected to be sustainability reporting standards on an international scale. The implementation of IFRS-SDS in Indonesia is commanded by Ikatan Akuntan Indonesia (IAI) by establishing the Task Force Comprehensive Corporate Reporting IAI (Task Force CCR IAI). The Task Force CCR IAI was formed to prepare standards and frameworks sustainability disclosure and reporting which will be adopted to be Comprehensive Corporate Reporting. The research aims to describe the growth between the topics of Accountants, Indonesia, and sustainability reporting with the quantitative method using the bibliometric analysis. The author also provide a model solving for the adoption strategy of the IFRS-SDS by using the qualitativedescriptive analysis. There have been significant growth about scientific topic in the last 10 years regarding the discourse between Accountants, Indonesia, and sustainability reporting. The author also provides several models of completion in the form of strategy, including (1) Harmonization of standards using the RAISE Method; (2) Design of Prospective — Retrospective Analysis; and (3) Use of Conceptual Sustainability reporting.